The Effect Of Demographic Factors And Comorbidities On Ejection Fraction Outcome In Acute Myocardial Infarction Patients - Kausar Malik; Faiza Batool; Shazia Siddiq; Lubna Meraj (Journal of Rawalpindi Medical College)
Objective: Left ventricular dysfunction commonly occurs as a complication after acute myocardial infarction. This study sought to explore the occurrence of acute left ventricular dysfunction among patients who have experienced an acute myocardial infarction (AMI)